1996
DOI: 10.1007/s002619900037
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal insufficiency with enlarged adrenals

Abstract: Five patients with adrenal insufficiency and large adrenal glands at presentation are reported. Addison's disease was due to adrenal tuberculosis in three patients, with important changes in adrenal configuration on CT reflecting the natural history of the disease. Adrenal infiltration by non-Hodgkin lymphoma and metastatic carcinoma of the lung was the cause of the disease in the fourth and fifth patients, respectively, who developed signs of adrenal insufficiency before the diagnosis of the primary lesion be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…On CT images, the involved adrenal glands are usually enlarged, which could be misdiagnosed as primary adrenal tumor. Although previous reports have described the CT features of adrenal tuberculosis, most of these studies were case reports with plain CT scans [2][3][4][5]. To the best of our knowledge, no study has analyzed the specific imaging criteria for differentiating tuberculosis from primary tumors in the adrenal glands.…”
Section: Introductionmentioning
confidence: 86%
“…On CT images, the involved adrenal glands are usually enlarged, which could be misdiagnosed as primary adrenal tumor. Although previous reports have described the CT features of adrenal tuberculosis, most of these studies were case reports with plain CT scans [2][3][4][5]. To the best of our knowledge, no study has analyzed the specific imaging criteria for differentiating tuberculosis from primary tumors in the adrenal glands.…”
Section: Introductionmentioning
confidence: 86%
“…Pathologic studies of the adrenals glands infected by tuberculous mycobacterium revealed caseous necrosis area and tuberculous granuloma at an early stage which causes destruction of the adrenal cortex leading to fibrosis and calcification (Efremidis et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Extrapulmonary occurrence of TB is estimated up to 15% [2] and endocrine glands are involved in 0.03% of extrapulmonary TB cases [4] . To the best of our knowledge, this rare pathological entity of adrenal insuffi ciency due to isolated adrenal TB is encountered in no more than six reports in the literature [1,[4][5][6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…The central hypoattenuating values represent areas of caseous necrosis [9] . In response to anti-TB therapy, the glands become gradually atrophic with irregular margins and usually develop calcifi cations (both appearing at least after 1 year of initiation of treatment) [5,9] .…”
Section: Discussionmentioning
confidence: 99%